TIPOLOGI PEMIKIRAN DAN MODEL TASAWUF SYAIKH MUTAMAKKIN KAJEN (KAJIAN SEMIOTIK DALAM BUKU PAKEM KAJEN) - Abdul Rosyid (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2019)
Syaikh Mutamakkin is one of the Javanese scholars that uses a local culture method as a media to spread Islam in Indonesia. It’s a method used Syaikh Mutamakkin written in the book of Pakem Kajen, a writing Pegon Javanese language that is a controversy for Javanese Islamic Scholars, in the end, must be tried in the Surakarta Keraton. The method used by Syaikh Mutamakkin is very interesting to research because he teaches Islam to society by Javanese anthropology that it’s a Sufism concept used Javanese traditional clothes analogy. The writer uses a semiotic approach because the analogy of Syaikh Mutamakkin is symbols of traditional clothes.